Monophosphoryl Lipid a Attenuates Multiorgan Dysfunction During Post-Burn Pseudomonas Aeruginosa Pneumonia in Sheep. Issue 3 (March 2020) - Fukuda, Satoshi; Ihara, Koji; Bohannon, Julia K.; Hernandez, Antonio; Patil, Naeem K.; Luan, Liming; Stothers, Cody; Stark, Ryan; Prough, Donald S.; Herndon, David N.; Sherwood, Edward R.; Enkhbaatar, Perenlei
ABSTRACT: Background: Monophosphoryl lipid A (MPLA) is a TLR4 agonist that has potent immunomodulatory properties and modulates innate immune function to improve host resistance to infection with common nosocomial pathogens in mice. The goal of this study was to assess the safety and efficacy of MPLA in a sheep model of burn injury and Pseudomonas aeruginosa pneumonia. The sheep provides a favorable model for preclinical testing as their response to TLR4 agonists closely mimics that of humans. Methods: Twelve chronically instrumented adult female Merino sheep received 20% total body surface area, third-degree cutaneous burn under anesthesia and analgesia. At 24 h after burn, sheep were randomly allocated to receive: MPLA (2.5 μg/kg i.v., n = 6), or vehicle (i.v., n = 6). At 24 h after MPLA or vehicle treatment, Pseudomonas aeruginosa pneumonia was induced. Sheep were mechanically ventilated, fluid resuscitated and cardiopulmonary variables were monitored for 24 h after induction of pneumonia. Cytokine production, vascular barrier function, and lung bacterial burden were also measured. Results: MPLA infusion induced small and transient alterations in core body temperature, heart rate, pulmonary artery pressure, and pulmonary vascular resistance. Pulmonary mechanics were not altered. Vehicle-treated sheep developed severe acute lung injury during Pseudomonas aeruginosa pneumonia, which was attenuated by MPLA as indicated by improved PaO2 /FiO2 ratio, oxygenation index, and shunt fraction. Sheep treated with MPLA also exhibited less vascular leak, lower blood lactate levels, and lower modified organ injury score. MPLA treatment attenuated systemic cytokine production and decreased lung bacterial burden. Conclusions: MPLA was well tolerated in burned sheep and attenuated development of acute lung injury, lactatemia, cytokinemia, vascular leak, and hemodynamic changes caused by Pseudomonas aeruginosa pneumonia. Abstract : Supplemental Digital Content is available in the text